Study of heavy atom influence on polyhalogenated compounds using DP4/MM-DP4+/ DP4+: insights and trends - Passaglia, Lucas (2024)
Fil: Passaglia, Lucas. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Química Rosario. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina